Holistic Medicine between Religion and Science: A Secularist Construction of Spiritual Healing in Medical Literature - Koch, Anne (Journal of religion in Europe, 2013)
A particular formation can be observed in the discourse of spiritual healing and complementary and alternative medicine (CAM). Explanations of the effectiveness of spiritual healing by medical doctors and psychologists sometimes include ideological and non-scientific conclusions and concepts, which are similar to but also different from New Age science on healing. With discourse analysis discursive nodes and strategies are identified in international medical and psychological research journals at the boundary of CAM, traditional medicine, and psychosomatics from the last decade. The article develops the category of secularism to describe these propositional formations and contributes to the larger debate of postsecular societies. Postsecularism not only puts public religion but also secularisms back on the agenda. This particular secularism in the field of spiritual healing is based on transfers of knowledge and practices between subareas of a functionally differentiated society: esoteric and scientific cultural models shift into medicine, and continue into the area of health care and healing. The article demonstrates how this secularism gathers around key concepts such as emergence, quantum physics, and physicalism, and is engaged in a permanent boundary work between conventional and alternative medicine, which is governed by the notion of holistic healing.